Review of knowledge to guide product development and breeding for sweetpotato frying quality in West Africa - Carey, E.E.; Ssali, R.T.; Low, Jan W. (Wiley, 2021)
ReviewReview of knowledge to guide product development and breedingfor sweetpotato frying quality in West AfricaEdward E. Carey,1* Reuben Ssali1& Jan W. Low21 International Potato Center (CIP) c/o CSIR-CRI, Fumesua, Kumasi 38785, Ghana2 International Potato Center (CIP), 00603, Nairobi 25171, Kenya(Received 17 July 2020; Accepted in revised form 9 December 2020)SummaryThis review provides background about sweetpotato in West Africa to identify the current importanceand future potential of sweetpotato fried products in the region. We drew on global literature to considercurrent best practices and health aspects in addition to information from West Africa where frying in theform of large wedges or ‘chunk fries’ is predominant over other forms (i.e. chips (often referred to ascrisps in England and the Commonwealth) and ‘French fries’). Chunk fries are produced mostly byfemale-run microenterprises selling them as a ﬁlling snack to roadside and market customers. Boiling, dry-ing and reconstituting in various foods, pounding and consumption of leaves as a vegetable are alsoimportant in the region. Further research will inform the development of a product proﬁle for chunk friedsweetpotato and inform breeding strategies to improve sweetpotato for frying and other uses.